Management Innovation and Principal Leadership in Private Junior High School - Muhammad Subhan Iswahyudi; Amrizal Amrizal; Akhmad Ramli; Merdi F. Mamonto; Sudadi Sudadi (Journal on Education, 2023)
The type of research used in this research is field case study research using a qualitative descriptive approach. Data collection was carried out through interview, observation, and documentation techniques. Data analysis includes data collection, data reduction, data presentation, and drawing conclusions. The findings from this study are that, first, management innovations carried out by school principals are in the areas of curriculum management, infrastructure management, and staffing management. Second, the leadership innovations carried out by the principal seem to be reflected in the principal as an innovative leader, with the dominant character being a friendly, democratic, intelligent principal who is good at seeing opportunities and building relationships. Third, innovation is carried out by school principals through three stages, namely initiating innovation programs, compiling innovation programs, and implementing innovations.